FOTODEGRADAÇÃO NO CLIMA SEMIÁRIDO EM FILMES DE POLI(BUTILENO ADIPATO-CO-TEREFTALATO) PUROS E ADITIVADOS COM ÓLEO ESSENCIAL DE CRAVO DA ÍNDIA (Syzygium aromaticum (L.) Merr.) - Karlos D. E. da Silva; Gabriel B. de L. Vitorino; Chaianne K. da S. Nascimento; Carlos A. de Souza; Amanda C. de O. D. Barros; Ivo D. de L. Silva; Glória M. Vinhas; José F. Q. Pereira; Andréa M. S. S. Brito (Química Nova)
PHOTODEGRADATION IN SEMI-ARID CLIMATE IN PURE POLY(BUTYLENE ADIPATE-CO-TEREPHTHALATE) FILMS AND ADDITIVES WITH CLOVE ESSENTIAL OIL (Syzygium aromaticum (L.) Merr.). Active packaging is a type of material used to extend the shelf life of food, due to its interaction with the product. This study evaluated the natural photodegradation of pure poly(butylene adipate-co-terephthalate) (PBAT) films and additives with 5% essential oil of clove Syzygium aromaticum (L.) Merr. (OEC). To this end, 96 samples were exposed to solar radiation in the municipality of Custódia in Sertão/PE, with fortnightly collections for 180 days, annual repetition in the same climatic period, and analyses in triplicates. All samples exhibited susceptibility to solar radiation, as evidenced by the appearance of cracks, fragmentation, and yellowing of the material. The samples were more sensitive to thermal action after exposure as determined by TGA. The mass loss exhibits an increasing trend, reaching a maximum average value of 13%. A decreasing trend was observed for the carbonyl index and a slight increase in the hydroxyl index. Principal component analysis revealed a distinction of samples exposed for more than 60 days. Overall, the results indicate a comparable degradation pattern between pure PBAT samples and additives with 5% OEC in a natural atmosphere environment of a semi-arid climate.